Internet testing for Chlamydia trachomatis in England, 2006 to 2010 - Woodhall Sarah C; Sile Bersabeh; Talebi Alireza; Nardone Anthony; Baraitser Paula (BMC, 2012)
Abstract Background In recent years there has been interest in websites as a means of increasing access to free chlamydia tests through the National Chlamydia Screening Programme (NCSP) in England. We aimed to describe and evaluate online access to chlamydia testing within the NCSP. Methods We analysed NCSP chlamydia testing data (2006-2010) for 15-24 year olds from the 71/95 programme areas in England where site codes were available to identify tests ordered through the internet. The characteristics of people using online testing services in 2010 were compared with those testing in general practice (GP) or community sexual and reproductive health (SRH) services. We evaluated 58 websites offering free chlamydia tests through the NCSP, and 32 offering kits on a commercial basis for signposting to clinical service and health promotion advice offered. Results Between 2006 and 2010, 5% of all tests in the included programme areas were accessed through the internet. The number of internet tests increased from 18 (<1% of all tests) in 2006 to 59,750 in 2010 (6% of all NCSP tests). In 2010 the proportion of NCSP tests accessed online by programme area ranged from <1% to 38%. The proportion of tests with a positive result on the internet was higher than tests from general practice and comparable to those from community SRH services (internet 7.6%; GP 5.6%; Community SRH 8.2%). A higher proportion of people accessing online testing were male, aged 20-24 and reported >1 sexual partner in the past year. Provision of sexual health information and appropriate signposting for those in need of clinical services varied between websites. Service provision within the NCSP was fragmented with multiple providers serving specific geographical catchment areas. Conclusion Internet testing reaches a population with a relatively high risk of chlamydia infection and appears acceptable to young men, a group that has been difficult to engage with chlamydia testing. In order to maximise the potential benefit of these services, websites should be consistent with national guidelines and adhere to minimum standards for signposting to clinical care and health promotion information. The current system with multiple providers servicing geographically specific catchment areas is contrary to the geographically unrestricted nature of the internet and potentially confusing for clients.